Podoba reformacije v slovenskem pripovedništvu na prelomu iz 19. v 20. stoletje s posebnim ozirom na Tavčarja - Čeh Steger, Jožica (Slavia Centralis, 2020)
The Image of Reformation in Slovene Literature at the Turn of the 19th and 20th Century with Specific Focus on Tavčar Slovene literature at the turn of the 19th and 20th Century portrays the images of Protestants not only as heretics deviating from true religion, but also as national opponents, supporters of the German culture and language. Namely, part of the Slovene public lived under the impression that the rise of Protestantism in the Slovene territory would consequently result in total Germanisation. Images of Protestantism in this period thus emerged in the form of foreignness, hostile to the native. Tavčar went even further and added a model of foreignness, which aimed at the assimilation of the foreign with the domestic. He verbalized this through real or arranged marriages of Slovene sons and German girls, and Catholic men and Lutheran women.
Keywords: reformation; Slovene narrative writing; image of foreignness; Tavčar; Cankar; Pregelj